2020
DOI: 10.1590/s0102-865020200040000008
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled study of the analgesic effect of intraoperative esmolol for laparoscopic gastroplasty

Abstract: To evaluate the analgesic effect of esmolol in patients submitted to laparoscopic gastroplasty. Methods: Forty patients aged between 18 and 50 years with American Society of Anesthesiologists (ASA) physical status scores of II and III who underwent gastric bypass were allocated to two groups. Group 1 patients received a 0.5-mg/kg bolus of esmolol in 30 mL of saline before induction of anesthesia, followed by an infusion at 15 µg/kg/min until the end of surgery. Group 2 patients received 30 mL of saline as a bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…26,27 Esmolol-induced continuous β-adrenergic receptor blockade leads to a more sparing use of opioid analgesics, which was demonstrated in the present study and other clinical trials alike. [28][29][30] In the current study, a very significant sparing of fentanyl and droperidol were registered.…”
Section: Discussionmentioning
confidence: 73%
“…26,27 Esmolol-induced continuous β-adrenergic receptor blockade leads to a more sparing use of opioid analgesics, which was demonstrated in the present study and other clinical trials alike. [28][29][30] In the current study, a very significant sparing of fentanyl and droperidol were registered.…”
Section: Discussionmentioning
confidence: 73%
“…The present study showed a significant opioid-sparing effect of esmolol and so did some other clinical trials. [21][22][23] Various publications even report on the decreased need for the administration of intravenous and inhalation anaesthetics as a result of esmolol iv bolus or infusion. 24,25 In the present study similar result was obtained, since there was a significantly lower need for isoflurane addition in the esmolol group, as compared to the control group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that esmolol, when used in continuous infusion, is effective in reducing undesirable hemodynamic effects such as hypertension and tachycardia during laryngoscopy maneuvers for orotacheal intubation [13][14][15]. Esmolol was also associated with lower intraoperative opioid consumption [16,17].…”
Section: Author Detailsmentioning
confidence: 99%